Putative protective neural mechanisms in prereaders with a family history of dyslexia who subsequently develop typical reading skills. Issue 10 (13th March 2020) - Yu, Xi; Zuk, Jennifer; Perdue, Meaghan V.; Ozernov‐Palchik, Ola; Raney, Talia; Beach, Sara D.; Norton, Elizabeth S.; Ou, Yangming; Gabrieli, John D. E.; Gaab, Nadine
Abstract: Developmental dyslexia affects 40–60% of children with a familial risk (FHD+) compared to a general prevalence of 5–10%. Despite the increased risk, about half of FHD+ children develop typical reading abilities (FHD+Typical). Yet the underlying neural characteristics of favorable reading outcomes in at‐risk children remain unknown. Utilizing a retrospective, longitudinal approach, this study examined whether putative protective neural mechanisms can be observed in FHD+Typical at the prereading stage. Functional and structural brain characteristics were examined in 47 FHD+ prereaders who subsequently developed typical ( n = 35) or impaired ( n = 12) reading abilities and 34 controls (FHD−Typical). Searchlight‐based multivariate pattern analyses identified distinct activation patterns during phonological processing between FHD+Typical and FHD−Typical in right inferior frontal gyrus (RIFG) and left temporo‐parietal cortex (LTPC) regions. Follow‐up analyses on group‐specific classification patterns demonstrated LTPC hypoactivation in FHD+Typical compared to FHD−Typical, suggesting this neural characteristic as an FHD+ phenotype. In contrast, RIFG showed hyperactivation in FHD+Typical than FHD−Typical, and its activation pattern was positively correlated with subsequent reading abilities in FHD+ but not controls (FHD−Typical). RIFG hyperactivation in FHD+Typical was further associated with increased interhemispheric functional and structural connectivity. These results suggest that some protective neural mechanisms are already established in FHD+Typical prereaders supporting their typical reading development.